Dysregulation of miR-146a: a causative factor in epilepsy pathogenesis, diagnosis, and prognosis - Mao, Shiqi; Wu, Jinhan; Yan, Jingkai; Zhang, Weijun; Zhu, Feng (Frontiers in Neurology, 2023)
miR-146a is an NF-κB-dependent miRNA that acts as an anti-inflammatory miRNA via the Toll-like receptor (TLR) pathway. miR-146a targets multiple genes and has been identified to directly or indirectly regulate processes other than inflammation, including intracellular Ca changes, apoptosis, oxidative stress, and neurodegeneration. miR-146a is an important regulator of gene expression in epilepsy development and progression. Furthermore, miR-146a-related single nucleotide polymorphisms (SNPs) and single nucleotide variants (SNVs) contribute to the genetic susceptibility to drug resistance and seizure severity in epilepsy patients. This study summarizes the abnormal expression patterns of miR-146a in different types and stages of epilepsy and its potential molecular regulation mechanism, indicating that miR-146a can be used as a novel biomarker for epilepsy diagnosis, prognosis, and treatment.